A New Algorithm to Treat Chronic Combined ACL/MCL Injuries: Let's Come Back to the "Rotatory Instability Test" - Nicolas Bouguennec MD; Thibault Marty-Diloy MD; Philippe Colombet MD; Nicolas Graveleau MD; James Robinson FRCS (Orth) (SAGE Publishing, 2023)
Background: Chronic combined medial collateral ligament (MCL) and anterior cruciate ligament (ACL) injuries are frequent. Medial residual laxity is a risk factor for ACL rerupture. It should be treated at the same time as the ACL reconstruction (ACLR) if necessary, but there are still questions surrounding the indications for abstention or surgery of the medial plan, especially for grade 2 MCL injuries of the Fetto and Marshall classification. Indications: The purpose is to come back to a simple test, the "Rotatory Instability Test" as described by Slocum and Larson in 1968 for systematic clinical examination of the knee to improve the sensitivity and accuracy of the deep MCL (dMCL) and superficial MCL (sMCL) examination and to propose a decision-making algorithm for the treatment of the chronic combined ACL/MCL injuries based on the assessment of anteromedial rotatory instability (AMRI). Technique Description: Examination of the ACL with Lachman test, anterior drawer in neutral rotation, and pivot shift test confirm the ACL injury. Valgus laxity is tested in extension and at 20° of flexion. Then, an anterior drawer test at 90° of flexion with external rotation is done (the anterior drawer in external rotation [ADER] test) allowing to identify isolated dMCL, dMCL + sMCL, or MCL + posterior oblique ligament (POL) injuries. Discussion: As persistent medial laxity is a risk factor for ACL graft failure and there is no reliable method of instrumented laxity assessment, careful clinical examination remains essential. Systematic examination of the medial side with valgus laxity testing at 0° and 20° flexion combined with the ADER test assessment of AMRI can guide treatment of the MCL injury component. Where there is no valgus laxity and the ADER test is negative, isolated ACLR is indicated. If there is significant medial laxity at 0°, this suggests combining sMCL and POL reconstruction with ACLR. Where the knee is stable at 0° but there is valgus laxity at 20° and a positive ADER test, the dMCL can be reconstructed using a gracilis graft or a combined sMCL and dMCL reconstruction can be added to the ACLR depending on the degree of laxity. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.